Psicociencias y gobierno de la subjetividad (2018)
ABSTRACT: This paper is an analysis of the disciplinarization process of the psychosciences and the manner in which they has been embedded into the practices of the governance of the subjects in western civilization. This research was conducted using a historical and critical approach based on Foucauldian genealogy.